2009
DOI: 10.1029/2008jc005153
|View full text |Cite
|
Sign up to set email alerts
|

Surf zone surface retention on a rip‐channeled beach

Abstract: [1] The retention of floating matter within the surf zone on a rip-channeled beach is examined with a combination of detailed field observations obtained during the Rip Current Experiment and a three-dimensional (3-D) wave and flow model. The acoustic Doppler current profiler-observed hourly vertical cross-shore velocity structure variability over a period of 3 days with normally incident swell is well reproduced by the computations, although the strong vertical attenuation of the subsurface rip current veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
105
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 41 publications
3
105
0
1
Order By: Relevance
“…At the DSZ, simulated zooplankters were concentrated in the surf zone by recirculation in an alongshore system of alternating shoals and rip currents [14][15][16]. Simulated zooplankters were transported into the surf zone over shoals, and they were concentrated in deeper rip channels before some returned seaward in offshore flow episodically with the arrival of wave groups.…”
Section: Discussionmentioning
confidence: 99%
“…At the DSZ, simulated zooplankters were concentrated in the surf zone by recirculation in an alongshore system of alternating shoals and rip currents [14][15][16]. Simulated zooplankters were transported into the surf zone over shoals, and they were concentrated in deeper rip channels before some returned seaward in offshore flow episodically with the arrival of wave groups.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to strengthening of existing rip currents or the generation of transient rip currents (MacMahan et al 2006, Johnson andPattiaratchi 2004). Moreover, the eddy like behavior of vortical VLF motions is found to significantly affect the mixing of material (larvae, nutrients, pollutants) inside the surfzone (Spydell et al 2007(Spydell et al ,2009) as well as the exchange of material with the shelf (Reniers et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the system morphology and the local wave climate, ocean waves may strongly impact dispersion processes. Surf zone transport and mixing affect the suspended matter alongshore distribution and nearshore retention [Boehm et al, 2005;Feddersen, 2007;Spydell et al, 2007Spydell et al, , 2009Reniers et al, 2009]. Waves also affect exchanges between the nearshore and the inner shelf [Lentz et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…In the nearshore, this leads to large vertical variations of the total cross-shore current. Also, laboratory and field observations suggested that rip currents might vary from depth-uniform to depth-varying outside the breakers, with higher velocities near the surface [e.g., Haas and Svendsen, 2002;Reniers et al, 2009]. To capture the transport of a tracer in the presence of waves, the vertical structure of the flow may thus be needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation